Digital HR Sustainability Model in Indonesian MSMEs and Employee Performance: Compensation, Leadership and Employee Retention - Devi, Putri Ayu Permata (International Journal of Business, Law, and Education, 2024)
This study looks into the connection between worker performance in Indonesian Micro, Small, and Medium-Sized Enterprises (MSMEs) and the Digital HR Sustainability Model (DHSM). The study uses partial least squares (PLS) path modeling to examine the direct and mediated impacts of employee retention, leadership, and compensation on the link between the DHSM and employee performance. It draws on a sample of 241 HR managers and senior management staff. The findings show that there is a strong positive correlation between employee performance and the DHSM and that this correlation is mediated by leadership, remuneration, and employee retention. The results highlight how crucial it is to adopt employee-centric and sustainable digital HR practices to improve organizational performance. By offering empirical proof of the mechanisms by which digital HR initiatives affect employee performance in the context of Indonesian MSMEs, the study adds to the body of current knowledge.